OPTIMALISASI KERJA PRAKTIK DALAM MENINGKATKAN KOMPETENSI MAHASISWA MELALUI PROGRAM MBKM PADA DINAS PENANAMAN MODAL DAN PELAYANAN SATU PINTU KABUPATEN BENGKAYANG - Dhea, Dhea; Dedy, Dedy (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2025)
The internship program is one of the essential activities to enhance students’ competencies through direct field experience in the Merdeka Belajar Kampus Merdeka (MBKM) program. Internship activities at the Investment and One-Stop Integrated Services Office (DPMPTSP) of Bengkayang Regency offer a strategic opportunity to bridge academic theory with real- world practices in the fields of public service and licensing. Through this program, students are able to experience the service process firsthand, improve their communication skills, and develop essential soft skills such as teamwork. The internship also helps cultivate students' character and work ethics. This study aims to evaluate the quality of services at the Public Service Mall (MPP) and explore how students' participation contributes to improving public service delivery. Moreover, MBKM-based internships not only enrich students’ learning experience but also prepare them to face real-world challenges and become more job-ready. The goal of MBKM is to ensure that graduates possess not only academic knowledge but also practical experience to serve as a valuable foundation for their future careers. Student involvement in this program can also contribute to service quality improvements, such as offering input on procedures and enhancing communication between officers and license applicants. MBKM optimizes the development of student competencies through practical experience in collaboration with government and industry, allowing them to simultaneously enhance both soft and hard skills.